Bibliometric Analysis of Public Leadership: Global Research Keyword Mapping (2019-2024) - Rahman, Nawir (Program Pascasarjana Universitas Negeri Makassar, 2024)
This study aims to analyze current public leadership trends using a bibliometric approach. This research is relevant given the importance of public leadership to achieve organizational goals through strategic planning, resource management, and its influence on subordinates. The main objective of the study is to identify keywords that frequently appear in the related literature, mapping relevant topics, around the world in the 2019–2024-time frame. The method used is to collect data through the Publish or Perish application from two main databases, namely Scopus and Google Scholar, then analyze it using Mendeley to identify author keywords. Further bibliometric analysis was carried out using VOSviewer to map the relationships between keywords and distribute the research geographically. The results showed that the keyword